Role of direct antiglobulin test in assessing the severity of extravascular hemolysis in autoimmune hemolytic anemia – analysis from a cross-sectional study - Anjaly Padmavilas Sasikala; Shaiji Panthiyil Shahulhameed; Sajith Vilambil; Usha Krishnakumariamma Chakrapani (Asian Journal of Medical Sciences, 2023)
Background: Autoimmune hemolytic anemia (AIHA) is an immune hemolytic disease characterized by hemolysis and anemia which results from increased red cell destruction due to auto antibodies directed against self-antigens on red cells. Clinical characteristics and potential associated hemolysis in AIHA can greatly depend on the serological characteristics. Aims and Objectives: This study was done to find out the association of Grade of polyspecific Direct Antiglobulin test (DAT), complement involvement and immunoglobulin G (IgG) subclass with severity of hemolysis in an AIHA patients. Materials and Methods: This was a cross-sectional study conducted for a period of 18 months from March 1, 2012, to August 31, 2013. Fifty consecutive AIHA patients diagnosed by a positive DAT in EDTA anticoagulated blood samples using poly specific anti human globulin reagent were followed up and results of various immunohematological tests such as polyspecific and monospecific DAT, IgG subtyping, and thermal amplitude were performed. Hematological and biochemical parameters such as hemoglobin, percentage of reticulocyte, total serum bilirubin, and serum lactate dehydrogenase also were recorded. Data were analyzed using SPSS v17. Results: Majority of patients were belonging to 31–40 year age group and there was a remarkable female predilection. Secondary AIHA was more common (56%) than primary. SLE was identified as the most common underlying disorder in secondary AIHA. Majority (46%) were Grade 4 DAT positive. Predominant autoantibody identified was IgG (52%). Of the total IgG positive cases, IgG1 was the predominant subclass. C3d alone was detected in 18% of cases and C3d and IgG together in 30%. About 48% of our patients were of warm type, 32% mixed type, and 20% cold type. About 80% of the study population were treated with steroids alone. A small percentage of cases (16%) needed immunosuppressant in addition to steroids and still a smaller percentage (4%) needed splenectomy. Higher grades of DAT positivity were associated with more severe degree of anemia and hyperbilirubinemia. The study also demonstrated a positive correlation between DAT grade and severity of hemolysis. Conclusion: AIHA patients in this study were predominantly of Warm AIHA with more of IgG1 involvement. A significant association is found between higher grades of DAT results and severity of anemia and jaundice in this study group. A positive correlation exists between grades of DCT and hemolysis as well.